Improving Service Quality in the Customer Journey by Developing Innovations of Information - Irwanto Irwanto (BPJS Kesehatan, 2021)
To improve the service process requires the latest innovation and creativity to answer the needs of participants. This research uses research and development (R&D) methods. All BPJS Health employees to carry out innovation initiatives by developing various methods to improve services to participants based on information technology that is easily accessible by participants anytime and anywhere. Most of our customers are millennials and tech-savvy (62%) so we need innovation in technology development to answer customer needs quickly and capture data. Hopefully with this technological innovation we can meet the needs and expectations of our participants, can provide services that are easier, faster and definitely without having to meet face to face.. Keywords: BPJS Kesehatan; Costumer; Technology Abstrak: Untuk meningkatkan proses pelayanan membutuhkan inovasi dan kreativitas terkini untuk menjawab kebutuhan peserta. Penelitian ini menggunakan metode penelitian dan pengembangan (R&D). Seluruh pegawai BPJS Kesehatan untuk melakukan inisiatif inovasi dengan mengembangkan berbagai metode untuk meningkatkan pelayanan kepada peserta berbasis teknologi informasi yang mudah diakses oleh peserta kapan saja dan dimana saja. Sebagian besar pelanggan kami adalah milenial dan melek teknologi (62%) sehingga kami membutuhkan inovasi dalam pengembangan teknologi untuk menjawab kebutuhan pelanggan dengan cepat dan menangkap data. Semoga dengan inovasi teknologi ini kami dapat memenuhi kebutuhan dan harapan para peserta kami, dapat memberikan pelayanan yang lebih mudah, cepat dan pasti tanpa harus bertatap muka.